THE EFFECTIVENESS OF DISTANCE LEARNING IN SCIENCE STUDENTS DURING COVID-19 AT SMPN KECAMATAN KOTO XI TARUSAN, PESISIR SELATAN DISTRICT ON UNDERSTANDING STUDENT CONCEPTS - mesi nastalia; Tuti Lestari (Department of Science Education, 2021)
Advances in science and technology (IPTEK), especially information technology an communication. Affects various areas of life, including education. In the era of the COVID-19 pandemic, the government asks all students in Indonesia to study at House. This research was conducted to describe the effectiveness of distance learning in science subjects during COVID-19 at SMPN Koto XI Tarusan Subdistrict, Pesisir Selatan Regency on students' conceptual understanding. The research instrument used a questionnaire in the form of a link in google form. Data retrieval techniques, namely data reduction, display data, and conclusion drawing / verification. ly readiness for independent learning and looking for more learning resources without face to face in school. Face-to-face learning is still not applicable during the COVID-19 pandemic. Distance learning facilities and infrastructure as well as economic and technological conditions are factors that affect distance learning so that distance learning which is carried out online has not been effective.